Existential identity and memory of a nation - Kačerauskas, Tomas (Creativity Studies, 2008)
The author affirms that the phenomena of history are always interpreted in the perspective of our future objectives. So, it is stated that the interpretation of nation’s history is the recollection of our future. Projection of the future grants us both creative dynamism (picturesqueness), and possibility of death (existential departure). According to another thesis, creating and existence form two planes of human reality, which create a living environment interacting between each other. The author affirms that this environment is the background of becoming of both individual and the nation, and it changes together with the phenomena emerging in it. According to the third thesis, existential participant’s space and time of existential participant ‐ individual or nation ‐ interact as his spiritual environment’s components of his becoming. The author follows individual’s and nation’s analogy, which means rather interaction when creating a living environment than similarity. Additionally, analogy includes aesthetic (sensual) aspect, which appears when talking about existential creativity. So, it is stated, that openness and incompleteness of existence is being supposed by the representation of our bodily (sensual) ending, in other words, by aesthetic tragedy. According to the author, the small individual circle and the big one of a nation are coupled by aesthetic tragedy. According to the fourth thesis, the being of a nation becomes meaningful when a nation becomes a hero in the face of its death. The conceptions of M. Heidegger (being towards death), M. Bachtin (hero, polyphonic interaction), E. Husserl (spiritual environment, phenomenon), Aristotle (dynamism, formation) and Plato (analogy, participation) are used in the research. Egzistencinis tapatumas ir tautos atmintis Santrauka. Straipsnio autoriaus teigimu, istorijos reiškiniai visada interpretuojami mūsų ateities siekių perspektyvoje, todėl tautos istorijos interpretacija čia suprantama kaip mūsų ateities prisiminimas. Ateities projekcija suteikia tiek kūrybinio judrumo (vaizdumo), tiek mirties (egzistencinio išėjimo) galimybę. Kita tezė: kūryba ir egzistencija sudaro dvi žmogiškos tikrovės plotmes, kurios sąveikaudamos kuria gyvenamą ją aplinką. Ši aplinka esanti tiek individo, tiek tautos tapatėjimo fonas, besikeičiantis drauge su jame kylančiais fenomenais. Trečioji tezė: egzistencijos dalyvio – individo ar tautos – erdvė ir laikas sąveikauja kaip jo tapatėjimo dvasinės aplinkos sandai. Vadovaujamasi tautos ir individo analogija, kuri reiškia ne tiek panašumą, kiek sąveiką kuriant gyvenamą ją aplinką. Be to, ši analogija apima estetinį (juslinį) aspektą, kuris randasi aptariant egzistencinę kūrybą. Todėl teigiama, kad egzistencijos neišbaigtumą ir atvirumą užtikrina mūsų kūniškos (juslinės) baigties vaizdinys, kitaip tariant, estetinis tragizmas. Individo mažojo ir tautos didžiojo egzistencinių ratų sankiba yra maitinama estetinio tragizmo. Ketvirtoji tezė: tautos būtis įprasminama, jai tapus heroje savo mirties akivaizdoje. Tyrinėjant egzistencinio tapatumo problemą, pasitelkiamos M. Heideggerio (būtis myriop), M. Bachtino (herojus, polifoninė sąveika), E. Husserlio (dvasinė aplinka, fenomenas), Aristotelio (judrumas, formavimas) ir Platono (analogija, dalyvavimas) koncepcijos. Reikšminiai žodžiai: tapatumas, egzistencija, atmintis, erdvė, laikas, aplinka. First Published Online: 14 Oct 2010